The effect of motor imagery on quality of movement when performing reaching tasks in healthy subjects: A proof of concept. (January 2022) - Kolářová, Barbora; Richards, Jim; Haltmar, Hana; Lippertová, Klára; Connell, Louise; Chohan, Ambreen
Abstract: Introduction: The use of motor imagery (MI) has been shown to offer significant improvements in movement performance in sports, and is now receiving a lot of attention as a relatively new therapeutic approach which can be applied in rehabilitation. However, the effects of MI on the quality of movement is still unclear. This study explored the immediate effect of MI on reaching tasks in healthy subjects. Methods: 17 healthy individuals (33 ± 8.2 years) participated in the study. Surface electromyography (sEMG) and inertial measurement units (IMU) were used to identify muscle activity and angular velocity in both upper limbs. Participants performed a reach task using their dominant and non-dominant arms at their most comfortable speed, they were then asked to imagine themselves performing the same reaching task, and finally they were asked to repeat the reaching task. Results: Significant decreases were seen in the muscle activity between pre and post MI for Biceps Brachii, Anterior Deltoid and Triceps Brachii. In addition, a significant increase was seen in extension angular velocity post MI. Discussion: The results indicate that the use of MI just after physical practice appears to have an immediate effect on the muscle activity and kinematics during a reaching task, which may suggest an improved quality of movement. Conclusion: This proof of concept study shows the potential for MI to improve the quality of performing reaching task and offers a possible therapeutic option for Stroke survivors and other neuromuscular disorders.